2023
DOI: 10.1159/000534751
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Periodontitis in US Adults: NHANES 2011–2014

Ling Liu,
Lin Yu Xia,
Yu Jie Gao
et al.

Abstract: <b><i>Introduction:</i></b> It is controversial whether obesity and periodontitis are related. A representative US population was examined for the relationship between obesity and periodontitis. <b><i>Methods:</i></b> In the National Health and Nutrition Examination Survey (NHANES) 2011–2014, participants (<i>n</i> = 6,662) aged 30 years or older and who underwent periodontal examinations were chosen for analysis. An assessment of obesity was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…The link between WWI and periodontitis was significant across both over and under 60 years groups but was more evident and had a more substantial effect size in the younger cohort. These results diverge somewhat from the previous studies by Liu et al and Al-Zahrani et al, which reported substantial links between obesity and periodontitis among young and middle-aged adults but not in the older population, using BMI and WC as indicators [ 11 , 12 ]. On the whole, the correlation between obesity and the incidence of periodontitis appears to be stronger in young and middle-aged individuals compared to older adults.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The link between WWI and periodontitis was significant across both over and under 60 years groups but was more evident and had a more substantial effect size in the younger cohort. These results diverge somewhat from the previous studies by Liu et al and Al-Zahrani et al, which reported substantial links between obesity and periodontitis among young and middle-aged adults but not in the older population, using BMI and WC as indicators [ 11 , 12 ]. On the whole, the correlation between obesity and the incidence of periodontitis appears to be stronger in young and middle-aged individuals compared to older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…This underlines the potential importance of appropriately evaluating obesity for predicting periodontitis risk and gauging disease severity. Liu et al’s investigation using NHANES data (2011–2014) found significant correlations between periodontitis and both BMI and WC, though this association was not evident in men [ 11 ]. However, Alsalihi et al and Kim et al did not find any link between periodontitis and BMI, but an association with WC, whereas Torrungruang et al reported no association between periodontitis and either BMI or WC [ 14 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodontal data obtained were analyzed and presented using descriptive statistics such as analysis of variance. In Table 1 , the continuous variables were presented as the mean (standard deviation) and the categorical variables were presented as the number (percentage) [3] , [4] , [5] , [6] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%